2017
DOI: 10.1016/j.clay.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the rheological properties of neat aqueous Wyoming sodium bentonite dispersions

Abstract: Temperature affects significantly the rheological behavior of neat water Wyoming Na-bentonite dispersions. The results of a very systematic study are presented regarding rheological measurements of 7% mass concentration at different temperatures, ranging between 25 and 80°C at atmospheric pressure. Higher temperature increased the shear stresses at low shear rates while the effect was much smaller at higher shear rates. The Herschel-Bulkley rheological model fitted extremely well all data. The yield stress inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 47 publications
(67 reference statements)
3
39
0
Order By: Relevance
“…Apparent viscosity, at all shear rates, also increased at higher temperatures. Addition of CM Fe3O4 NP at 0.5 wt % showed optimal filtration characteristics with a reduction of 40% of fluid Vryzas et al [20,21] that were used as base fluid in this study was reported in other studies [9,22]. They found that the yield stress and apparent viscosity, at all shear rates, became increasingly sensitive to temperature.…”
Section: Experimental Studiessupporting
confidence: 56%
See 3 more Smart Citations
“…Apparent viscosity, at all shear rates, also increased at higher temperatures. Addition of CM Fe3O4 NP at 0.5 wt % showed optimal filtration characteristics with a reduction of 40% of fluid Vryzas et al [20,21] that were used as base fluid in this study was reported in other studies [9,22]. They found that the yield stress and apparent viscosity, at all shear rates, became increasingly sensitive to temperature.…”
Section: Experimental Studiessupporting
confidence: 56%
“…Addition of Vryzas et al [20,21] investigated novel custom-made (CM) magnetite (Fe3O4) NP ( Figure 8a) as drilling fluid additives, with diameters of approximately 8 nm, to improve the rheological and filtration properties of Na-bentonite based fluids. Full characterization of Na-bentonite suspensions that were used as base fluid in this study was reported in other studies [9,22]. They found that the yield stress and apparent viscosity, at all shear rates, became increasingly sensitive to temperature.…”
Section: Experimental Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…In our experiment, there was no apparent change in the rheological parameters within the temperature range of 2–30°C, which is consistent with the results of Coussot and Piau (). At higher temperatures, of up to 80°C, Vryzas et al () reported a gradual strengthening in the yield stress and reduced viscosity of sodium montmorillonite dispersions. The authors argued that thermally activated Brownian motion may cause flexures and strong associations between the smectite platelets, which may in turn cause a higher yield stress at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%